Analysis of Consumer Attitude on Online Ticket Using Fishbein Method - Ary Meizari (Proceeding International Conference on Information Technology and Business, 2018)
The development of internet today reaches almost a half of the population in Indonesia so that business sectors take advantage of this development through online businesses. One of the opportunities that the business sectors take is e-ticketing or online business. The ticket sales services are now transformed into the electronic ticket or e-ticketing known as Online Travel Agent (OTA). The objective of this research was finding out the consumer attitude on Traveloka, PegiPegi.com and Tiket.com. The sampling technique used in this research was the nonprobability and the accidental sampling technique. The data analysis technique used in this research was the fishbein analysis. The result of this research showed that the score of the consumer attitude on the traveloka was ordinary; the score of the consumer attitude on PegiPegi.com was ordinary; and, the value of the consumer attitude on the Tiket.com was good. Thus, Tiket.com had a reasonable attitude for the consumer compared to the other servicesKeywords: Consumer Attitude, Online Ticket, Fishbein Methods